Laravel Filament-Based Driver Commission Management and Calculation System Automation - Alfito Aditya Trishardi (COREAI: Jurnal Kecerdasan Buatan, Komputasi dan Teknologi Informasi, 2026)
Mentari Restaurant relies on delivery services provided by drivers as part of its daily operations; however, the processes for recording deliveries and calculating driver commissions—ranging from data compilation to payment processing—are still handled manually. This approach leaves the system vulnerable to calculation errors, data opacity, and payment delays, while the lack of an integrated system hinders comprehensive monitoring of driver performance. This research developed a web-based Driver Commission System using the Laravel framework and the Laravel Filament administration panel. The system automates delivery logging, commission calculations, driver data management, and reporting within a single integrated platform, utilizing the Iterative Waterfall development method and data collection techniques such as observation, interviews, and document analysis. Black-box testing across sixteen scenarios demonstrated that all system functions (100%) operated as required; consequently, the system is expected to provide a concrete solution for improving commission calculation accuracy, accelerating payment processes, and strengthening trust between drivers and Mentari Restaurant management.